hmm, let me sketch this out:

To prove A and BuC are in dependant, BuC must equal BuC | A |

(BTW, | is given, so BuC given A must equal BuC) |

General: X | Z = (XnZ) / Z |

BuC | A = (BuC n A) / A |

When A and B dependant , AnB = A|B * B

When A and B independent AnB = A*B

So

BuC | A = (BuC * A) / A

BuC | A = BuC

Therefore, BuC is independant of A

(I hope that’s what you’re after)

Can you help plz..

i dont know how to prove this:

A,B,C are 3 independent events.

We must prove that A and BUC are independent too

link